Growth of Monolayer WS2Single Crystals with Atmospheric Pressure CVD: Role of Temperature - Xie, Yong; Wang, Guanfei; Wang, Zhan; Nan, Tang; Wang, Haolin; Wang, Yabin; Zhan, Yongjie; Jie, Wanqi; Ma, Xiaohua (MRS Advances, 2019)
It has been demonstrated that the introduction of NaCl can significantly improve the quality of monolayer WS 2 at the growth temperatures ranging from 700°C to 850°C by atmospheric pressure chemical vapor deposition (APCVD) without the assistant of hydrogen. Here, the influence of NaCl on the nucleation and growth of WS 2 has been thoroughly investigated. The morphology and quality of WS 2 grown with different temperatures are discussed by optical microscope, Raman and Photoluminescence (PL) spectra. It was found that amount of NaCl can efficiently influence the morphology and quality of WS 2 crystals. PL intensity of WS 2 crystal increases around three times from the center region to the edge of an individual domain, which may be attributed to the appearance of small triangle hollows formed during the growth at the edge of single crystal WS 2 .
CRIS-Team Scopus Importer:2019-05-09
Keywords: 2D materials; chemical vapor deposition (CVD) (deposition); optical properties; scanning electron microscopy (SEM)